2022
DOI: 10.48550/arxiv.2204.06937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CO Emission, Molecular Gas, and Metallicity in Main-Sequence Star-Forming Galaxies at $z\sim2.3$

Abstract: We present observations of CO(3−2) in 13 main-sequence z = 2.0 − 2.5 star-forming galaxies at log(M * /M ) = 10.2 − 10.6 that span a wide range in metallicity (O/H) based on rest-optical spectroscopy. We find that L CO(3−2) /SFR decreases with decreasing metallicity, implying that the CO luminosity per unit gas mass is lower in low-metallicity galaxies at z ∼ 2. We constrain the CO-to-H 2 conversion factor (α CO ) and find that α CO inversely correlates with metallicity at z ∼ 2. We derive molecular gas masses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 169 publications
(346 reference statements)
0
2
0
Order By: Relevance
“…This scenario is supported by observations and simulations that have shown that several major galaxy properties correlate, forming so-called scaling relations. Amongst the most notable correlations, those of interest for this work are: (i) the correlation between 𝑀 ★ and SFR, dubbed the "main sequence" (MS; Noeske et al 2007, Elbaz et al 2011, Speagle et al 2014, Whitaker et al 2014, Renzini & Peng 2015, Boogaard et al 2018 the correlation between 𝑀 ★ and gas metallicity, referred to as the "mass-metallicity relation" (MZR; Tremonti et al 2004, Maiolino et al 2008, Erb et al 2006, Zahid et al 2011, Sanders et al 2022. The MS shows that 𝑀 ★ and SFR are positively correlated, meaning that an increasing stellar mass is directly linked to an increasing SFR, over 10 7 M ≤ 𝑀 ★ ≤ 10 11.5 M .…”
Section: Introductionmentioning
confidence: 99%
“…This scenario is supported by observations and simulations that have shown that several major galaxy properties correlate, forming so-called scaling relations. Amongst the most notable correlations, those of interest for this work are: (i) the correlation between 𝑀 ★ and SFR, dubbed the "main sequence" (MS; Noeske et al 2007, Elbaz et al 2011, Speagle et al 2014, Whitaker et al 2014, Renzini & Peng 2015, Boogaard et al 2018 the correlation between 𝑀 ★ and gas metallicity, referred to as the "mass-metallicity relation" (MZR; Tremonti et al 2004, Maiolino et al 2008, Erb et al 2006, Zahid et al 2011, Sanders et al 2022. The MS shows that 𝑀 ★ and SFR are positively correlated, meaning that an increasing stellar mass is directly linked to an increasing SFR, over 10 7 M ≤ 𝑀 ★ ≤ 10 11.5 M .…”
Section: Introductionmentioning
confidence: 99%
“…While the scenario of 'expulsive' AGN feedback is not fully backed up by observations (e.g. Sanders et al 2022), alternative manifestations of AGN feedback have recently been gaining consensus. For instance, compact (<1 kpc), low-power radio jets have been widely observed in local ('radio-quiet') Seyferts (e.g.…”
Section: Introductionmentioning
confidence: 99%